Towards Safer and More Productive Migration for South Asia - World Bank (World Bank, Washington, DC, 2020)
International migration for temporary employment is a critical component of South Asia’s development path, from both the jobs and remittance flows perspectives. South Asian economies are at a stage of demographic transition where people of working-age are generally still increasing shares of populations, with millions of people entering the working-age cohort every year for another generation. This report focuses on Bangladesh, Nepal, and Pakistan - three countries in the region sharing similar characteristics, opportunities, and challenges when it comes to international migration. All three are lower-middle income countries where sizeable shares of the working age population migrate overseas. Migration has large positive effects on South Asian economies overall, often noted by the fact that remittances tend to be very high in relative and absolute terms. Several of the policy actions that can be taken in the pre-migration phase of the migration life-cycle to reduce the vulnerability of migrants will directly reduce costs and improve access for poorer households. Reducing volatility and improving sustainability will require sending countries to ultimately diversify the markets where they send their workers.